(untitled) (Research, Society and Development, 2022)
This bibliographic review study aimed to analyze scientific articles on congenital malformation of the pulmonary airways indexed in the Biblioteca Virtual de Saúde (BVS), Scientif Electronic Library Online (SciELO), National Library of Medicine (PubMed), EbscoHost and Google Scholar from 2012 to 2022. The sample consisted of 20 articles that were analyzed in terms of study design and theme. Therefore, it is concluded that the cystic adenomatoid malformation is a rare condition that varies in its clinical form of manifestation, from a respiratory dysfunction in the postnatal period to an incidental radiographic finding in adult life, in the period in which the symptoms appear and in the degree of lung development. Therefore, in view of its complexity, it still needs to be explored regarding its evolution, treatment and prognosis so that its damage is reduced.